2004
DOI: 10.1183/09031936.04.00014004
|View full text |Cite
|
Sign up to set email alerts
|

Primary pulmonary lymphangiectasia in infancy and childhood

Abstract: Primary pulmonary lymphangiectasia (PPL) is a rare disorder of unknown aetiology characterised by dilatation of the pulmonary lymphatics. PPL is widely reported to have a poor prognosis in the neonatal period and little is known about the clinical features of patients who survive the newborn period.The current authors report the outcome in nine patients diagnosed in infancy with PPL over a 15-yr period at a single university-based hospital clinic and followed for a median of 6 yrs.Although all of the patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 28 publications
0
56
0
Order By: Relevance
“…In the last few years, an increasing number of patients with primary PL who survived were reported. However, they are different from our case in that they had either a better overall clinical course (with no hydrops), were syndromic, diagnosed after the neonatal period or never confirmed by lung biopsy [8][9][10] . As far as we know, this is the first reported case of a patient with hydrops fetalis (requiring prenatal intervention), immediate postnatal onset of respiratory failure and primary PL confirmed by lung biopsy that survived the neonatal period and was discharged home without oxygen requirements.…”
Section: Discussionmentioning
confidence: 43%
“…In the last few years, an increasing number of patients with primary PL who survived were reported. However, they are different from our case in that they had either a better overall clinical course (with no hydrops), were syndromic, diagnosed after the neonatal period or never confirmed by lung biopsy [8][9][10] . As far as we know, this is the first reported case of a patient with hydrops fetalis (requiring prenatal intervention), immediate postnatal onset of respiratory failure and primary PL confirmed by lung biopsy that survived the neonatal period and was discharged home without oxygen requirements.…”
Section: Discussionmentioning
confidence: 43%
“…Of the four reported cases, including this one, three resulted in death, and the outcome after treatment was not reported in one. In contrast, BARKER et al [9] have suggested that the prognosis of CPL with post-neonatal onset is excellent. This divergence may show that the clinical behaviour and prognosis of CPL depend on the extent of pulmonary involvement of the lymphatic dilatations and/or to other still unknown factors.…”
Section: Answermentioning
confidence: 90%
“…It will usually present with respiratory symptoms like persistent tachypnea, recurrent cough or wheeze or airway infections. In patients with an early diagnosis of CPL and without significant associated congenital anomalies follow up studies have shown that long-term survival can be expected [28,43] with improving respiratory status. In lung function tests, restrictive and obstructive patterns have been described with relative stability over time [43].…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 98%